Test design to measure the cognitive processing speed of table tennis players - Mohsen, Z. Z.; Maleh, F. A. (Journal of Human Sport & Exercise, 2020)
Table tennis is considered one of the fast base sports that the player needs to have the speed of performance and awareness, especially in straight forward and back strikes, which is an important offensive skills, and the player success depends on his perception speed to the point of the fall of the ball in the arena of his competitor. But there is no way to measure cognitive processing speed. Therefore, the researchers sought to design a test that measures this ability to ensure its scientific evaluation, and then establish standard scores for this test for the players of the specialized school of table tennis, to help evaluate them objectively and move away from subjective estimates when evaluating and developing measuring instruments in the field of table tennis. The descriptive curriculum was adopted on the 46 players of the table tennis school. After the exploratory experiment was conducted and confirmed the test validity and the availability of scientific specifications, it was applied to the sample taking into account all legal procedures during the implementation of the final test and then collected the results and was discharged and processed statistically, and the researchers concluded: The test designed proved to be valid for measuring cognitive processing speed. The research sample achieved a higher percentage at an acceptable and average level, respectively. So, the researchers recommend using the test designed to measure cognitive processing speed.